Assortment research of analgesic drugs for chronic pain treatment on pharmaceutical market of Ukraine - I. V. Zupanets; O. A. Ruban; O. M. Ievtushenko; Т. E. Kolisnyk (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Chronic pain reduces patients' life quality, affects their social and productive function in the state for a long period of time, or even for a whole lifetime. For the chronic pain treatment analgesic medications of symptomatic action are prescribed. According to international guidelines, paracetamol is one of the first line drugs. Aim - сonducting an assortment analysis of pharmaceutical medicines of Ukraine that can be used for the treatment of сhronic pain. Search for combined analgesics with hepatoprotective activity for the treatment of сhronic pain. Information sources: State Register of Medicines of Ukraine, Compendium web site. The analysis was conducted using content analysis and marketing research. Data processing and graphical analysis were performed in MS Excel software. During the marketing analysis of the registered in Ukraine medicines that can be used for mild and moderate сhronic pain treatment, the international non-proprietary names, listed in the national protocol of Ukraine, were selected. According to the ATC classification, these are groups N02B (non-narcotic analgesics) and M01A (non-steroidal anti-inflammatory and antirheumatic agents). N02B group has 245 registered drugs, 53.06% of which are produced domestically. Group M01A consists of 392 trade names that can be used for сhronic pain therapy. The ratio of Ukrainian manufacturers is only 39.80%, while foreign ones - 60.20%. For the treatment of сhronic pain tablet or capsule dosage forms are used. The market of analgesic products of Ukraine that can be used for сhronic pain therapy has been analyzed. It is established that the pharmaceutical market of Ukraine is import-dependent and promising for domestic enterprises. In Ukraine there are no drugs with paracetamol in combination with hepatoprotective ingredients and preparations directed exceptionally to сhronic pain treatment. In addition, there are practically no drugs of this direction in modern dosage forms (orally disintegrating tablets, soluble tablets, modified-release tablets, etc.) that improve patient compliance. All this is the basis for increasing the assortment of products in modern dosage forms.